MEDIASI SEBAGAI SOLUSI ALTERNATIF KONFLIK KELUARGA PERSPEKTIF HUKUM ISLAM DAN HUKUM PROGRESIF - Achmad Alfan Kurniawan (Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan., 2022)
Mediation is a fast, cheap, and satisfying alternative in resolving disputes. In reality, however, the opposite of these hypotheses occurs. As a result, a holistic understanding of mediation is required so that in the future, mediation can exist progressively in handling, reducing, and resolving family conflicts, thereby achieving the ideals of sakinah mawaddah warahmah in the family. The purpose of this paper is to analyse mediation through the perspective of Islamic law and progressive law. The analysis’s findings, which were obtained using normative methods and an analytical-descriptive approach, demonstrate that, from the perspective of Islamic law, the current model of mediation is the result of the integration of sulh and tahkim which the process of disputing parties negotiating with the assistance of a mediator who facilitates and controls the process to reach a consensual agreement. Sulh describes the characteristics of reaching a consensual agreement, while tahkim describes the characteristics of appointing a third party as a mediator. Meanwhile, according to progressive law, mediation is a creative, innovative, productive, fair, and dynamic means of resolving family conflicts. So mediation exists and is progressive as an institution that serves humans and solves problems in order for them to be happy.